Senior Thai Fecal Microbiota Comparison Between Vegetarians and Non-Vegetarians Using PCR-DGGE and Real-Time PCR - Ruengsomwong, Supatjaree; Korenori, Yuki; Sakamoto, Naoshige; Wannissorn, Bhusita; Nakayama, Jiro; Nitisinprasert, Sunee (Journal of microbiology and biotechnology, 2014)
The fecal microbiotas were investigated in 13 healthy Thai subjects using polymerase chain reaction denaturing gradient gel electrophoresis (PCR-DGGE). Among the 186 DNA bands detected on the polyacrylamide gel, 37 bands were identified as representing 11 species: Bacteroides thetaiotaomicron, Bacteroides ovatus, Bacteroides uniformis, Bacteroides vulgatus, Clostridium colicanis, Eubacterium eligenes, E. rectale, Faecalibacterium prausnitzii, Megamonas funiformis, Prevotella copri, and Roseburia intestinalis, belonging mainly to the groups of Bacteroides, Prevotella, Clostridium, and F. prausnitzii. A dendrogram of the PCR-DGGE divided the subjects; vegetarians and non-vegetarians. The fecal microbiotas were also analyzed using a quantitative real-time PCR focused on Bacteroides, Bifidobacterium, Enterobacteriaceae, Clostrium coccoides-Eubacterium rectale, C. leptum, Lactobacillus, and Prevotella. The nonvegetarian and vegetarian subjects were found to have significant differences in the high abundance of the Bacteroides and Prevotella genera, respectively. No significant differences were found in the counts of Bifidabacterium, Enterobacteriaceae, C. coccoides-E. rectale group, C. leptum group, and Lactobacillus. Therefore, these findings on the microbiota of healthy Thais consuming different diets could provide helpful data for predicting the health of South East Asians with similar diets.